2012
DOI: 10.1080/01430750.2011.636209
|View full text |Cite
|
Sign up to set email alerts
|

Influence of static injection timing on combustion, emission and performance characteristics of DI diesel engine fuelled with honne oil methyl ester

Abstract: This study is aimed to investigate experimentally the combustion, exhaust emissions and performance characteristics of a direct injection (DI) diesel engine, typically used in the agricultural sector, when fuelled with neat diesel (ND), and abundantly available but untapped honne oil methyl ester (HOME) is used in diesel engines. The static injection timing (SIT) is varied from 23 crank angle (CA) (manufacturer's specified value) to 28 CA. The combustion parameters of HOME improved as SIT increased. The brake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The diesel engine powered with B40 blend biodiesel results in higher BTE than diesel with respect to combinations of CR 18, IOP 240 bar and advanced IT 26° BTDC (Kumar et al, 2016). The diesel engine powered with hone oil methyl ester has given higher BTE is less than that of neat diesel fuel, mean while reduced emissions (smoke opacity (SO), CO, HC and NOx) was observed at advanced IT from 27 to 28 CA bTDC (Belagur and Chitimini, 2012). The diesel engine powered with blend of calophyllum inophyllum methyl ester has given higher thermal efficiency and SFC for 3 and 4 holes injectors at 250 bar IOP, at the same time substantial reduction of harmful pollutants levels for 5 holes nozzle operated 250 bar IOP (Vairamuthu et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…The diesel engine powered with B40 blend biodiesel results in higher BTE than diesel with respect to combinations of CR 18, IOP 240 bar and advanced IT 26° BTDC (Kumar et al, 2016). The diesel engine powered with hone oil methyl ester has given higher BTE is less than that of neat diesel fuel, mean while reduced emissions (smoke opacity (SO), CO, HC and NOx) was observed at advanced IT from 27 to 28 CA bTDC (Belagur and Chitimini, 2012). The diesel engine powered with blend of calophyllum inophyllum methyl ester has given higher thermal efficiency and SFC for 3 and 4 holes injectors at 250 bar IOP, at the same time substantial reduction of harmful pollutants levels for 5 holes nozzle operated 250 bar IOP (Vairamuthu et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…Kannan et al [21] have found that the collective effect of high IPR and an advanced ITG brings out in improved BTE, cylinder gas pressure (CGP), Heat Release Rate (HRR) and reduced NOx and Particulate matter from Waste Cooking oil biodiesel. Venkanna Krishnamurthy Belagur et al [22] conducted an experimental study using Honne Oil Methyl Ester (HOME) with diesel. From their research, they reported that the increased ITG had improved combustion parameters leading to increasing BTE and reduction in emissions.…”
Section: Introductionmentioning
confidence: 99%